UNMET NEED FOR FAMILY PLANNING PROGRAM; A SITUATIONAL ANALYSIS OF BIRTH SPACING AND LIMITING AMONG REPRODUCTIVE AGE WOMEN IN PANGKALPINANG CITY, BANGKA BELITUNG PROVINCE INDONESIA - Antarini, Antarini; Masfiah, Siti; Fitriani, Ayu; Junaidi, Lili (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Population growth, become one of priority problems, should be solved in almost all of developing countries, including Indonesia. In 2007, unmet need was 8.6%, inclined to 11.4% in 2015, which is consisted of 4.5% for spacing children and 8.6% for limiting children. Social demography, economic, access to health services, family support and perception revealed have the contribution to unmet need. Aims: This study aimed to explore unmet need family planning due to birth spacing and limiting situation among reproductive age women in Pangkal Pinang City, Bangka Belitung Province. Methods: It was survey research used cross-sectional design. The population was women of childbearing age who experienced unmet need of family planning in Pangkal Pinang, 2016. A total of 98 women was taken by proportional random sampling to participate in this study. Data was analyzed using descriptive statistics and used to report the results in the form of frequency distribution and percentage (%) of each item. Results: Research showed that the most of the unmet need for family planning was among 25-29 years old women. About two third (66.3%) of unmet need women occurred due to the willingness to space the childbirth and 33.7% willing to limit the childbirth. Birth spacing tended to be favored by young mothers, early marriage (1-5 years old), had low parity and had low education attainment. Whilst, limiting childbirth tended to be preferred by women with lenght of marriage experience (>15 years old), had high parity, older mothers, and secondary education level (senior high school) attainment. Both of spacing and limiting have no difference according to the economic situation. All of them mostly were the household wife from low-income family. Husband support to not use contraception was found in both birth spacing and birth limiting. Conclusion: The study suggests to provincial health office and national family planning coordination board that family planning program should not just involve the wife, but husband as well due to their high influence in family planning decision.Â